A novel thermostable polymerase for RNA and DNA loop-mediated isothermal amplification (LAMP) - Chander, Yogesh; Koelbl, Jim; Puckett, Jamie; Moser, Michael J.; Klingele, Audrey J.; Liles, Mark R.; Carrias, Abel; Mead, David A.; Schoenfeld, Thomas W. (Frontiers in Microbiology, 2014)
Meeting the goal of providing point of care (POC) tests for molecular detection of pathogens in low resource settings places stringent demands on all aspects of the technology. OmniAmp DNA polymerase (Pol) is a thermostable viral enzyme that enables true POC use in clinics or in field by overcoming important barriers to isothermal amplification. In this paper, we describe the multiple advantages of OmniAmp Pol as an isothermal amplification enzyme and provide examples of its use in loop-mediated isothermal amplification (LAMP) for pathogen detection. The inherent reverse transcriptase activity of OmniAmp Pol allows single enzyme detection of RNA targets in RT-LAMP. Common methods of nucleic acid amplification are highly susceptible to sample contaminants, necessitating elaborate nucleic acid purification protocols that are incompatible with POC or field use. OmniAmp Pol was found to be less inhibited by whole blood components typical in certain crude sample preparations . Moreover, the thermostability of the enzyme compared to alternative DNA polymerases (Bst) and reverse transcriptases allows pretreatment of complete reaction mixes immediately prior to amplification, which facilitates amplification of highly structured genome regions. Compared to Bst, OmniAmp Pol has a faster time to result, particularly with more dilute templates. Molecular diagnostics in field settings can be challenging due to the lack of refrigeration. The stability of OmniAmp Pol is compatible with a dry format that enables long term storage at ambient temperatures. A final requirement for field operability is compatibility with either commonly available instruments or, in other cases, a simple, inexpensive, portable detection mode requiring minimal training or power. Detection of amplification products is shown using lateral flow strips and analysis on a real-time PCR instrument. Results of this study show that OmniAmp Pol is ideally suited for low resource molecular detection of pathogens.